2021
DOI: 10.1002/jqs.3290
|View full text |Cite
|
Sign up to set email alerts
|

Not herbs and forbs alone: pollen‐based evidence for the presence of boreal trees and shrubs in Cis‐Baikal (Eastern Siberia) derived from the Last Glacial Maximum sediment of Lake Ochaul

Abstract: A new accerator mass spectrometry (AMS)‐dated sedimentary record from Lake Ochaul (54°14′N, 106°28′E; 641 m a.s.l.) in Eastern Siberia covers the interval from ca. 27 850 to 20 400 cal a bp at ca. 180‐year resolution and contributes to a better understanding of the complex spatial vegetation pattern during the Last Glacial Maximum (LGM). Non‐arboreal pollen taxa are abundant in the pollen assemblages (mean value ca. 92.6%), but boreal trees are represented by all major taxa that grow in the lake catchment toda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…According to paleobiological records Siberia was a dry desert interspersed with pockets of forested areas (Semerikov et al 2013 and reference there in). Still, Karunarathne et al (2023) suggested that the southern part of the Siberian Plain was a suitable habitat for Siberian spruce during glacial periods and the presence of spruce during the LGM in the Baikal region is attested by fossil pollen (Kobe et al 2022). Using niche modelling and backward climate projection, Karunarathne et al (2023) also suggested that the distribution ranges of P. abies and P. obovata overlapped during interglacial periods in their Northern range (~145 kya).…”
Section: Two Ancient Cryptic Refugia Bridge P Abies and P Obovata Gen...mentioning
confidence: 99%
“…According to paleobiological records Siberia was a dry desert interspersed with pockets of forested areas (Semerikov et al 2013 and reference there in). Still, Karunarathne et al (2023) suggested that the southern part of the Siberian Plain was a suitable habitat for Siberian spruce during glacial periods and the presence of spruce during the LGM in the Baikal region is attested by fossil pollen (Kobe et al 2022). Using niche modelling and backward climate projection, Karunarathne et al (2023) also suggested that the distribution ranges of P. abies and P. obovata overlapped during interglacial periods in their Northern range (~145 kya).…”
Section: Two Ancient Cryptic Refugia Bridge P Abies and P Obovata Gen...mentioning
confidence: 99%
“…On the basis of other pollen records, however, the Baikal region during this time became open and almost treeless, characterized by sparse tundra-steppe vegetation and the expansion of permafrost [e.g., (22,35)]. When comparing the herb pollen spectra for the LGM in Cisbaikal and Transbaikal, however, Kobe et al (62) found that Transbaikal was notably drier than Cisbaikal, with the Poaceae-enriched grassland of Cisbaikal potentially sustaining the mammoth-steppe fauna. Human populations persisted, too, especially in Cisbaikal where some of the largest MUP settlements interpreted as residential base camps [not only Mal'ta but also possibly Alekseevsk, Buret', and Igeteiskii Log-1 (63)(64)] continued to be occupied right up to the LGM, 26.5 to 24.5 ka ago.…”
Section: Human Dispersal and Settlement During Mis 3 And Early Mis 2 ...mentioning
confidence: 99%
“…The outflow of the lake, Syan River, Figure 1. Location of Lake Emanda and positions of mentioned sites: 1 -Lake Billyakh (Müller et al, 2010;Diekmann et al, 2017); 2 -Dyanushka (Zech et al, 2011); 3 -Batagay (Ashastina et al, 2018); 4 -Lake Smorodinovoye (Anderson et al, 2002); 5-6paleoenvironmental records from arctic Yakutia (Andreev et al, 2002(Andreev et al, , 2009(Andreev et al, , 2011; 7 -Lake El'gygytgyn (Lozhkin et al, 2006;Anderson and Lozhkin and Anderson, 2011;Melles et al, 2012):); 9 -Lake Kotokel (Tarasov et al, 2021); 10 -Lake Ochaul (Kobe et al, 2022). [Color figure can be viewed at wileyonlinelibrary.com] a right-hand tributary of the Derbeke River (part of the Yana River basin) drains the lake to the north.…”
Section: Study Sitementioning
confidence: 99%